Regulation of gene expression under high hydrostatic pressure: the versatile role of the master regulator SurR in energy metabolism - Moalic, Yann; Nguyen, Toan Bao Hung; Hartunians, Jordan; Birien, Tiphaine; Thiel, Axel; Jebbar, Mohamed (Frontiers in Microbiology, 2025)
In Thermococcales, energy metabolism genes are regulated by the sulfur-responsive transcriptional regulator SurR. In the piezophilic archaeon Thermococcus barophilus, these genes are also influenced by hydrostatic pressure. To explore the interaction between pressure, sulfur availability, and gene regulation, we constructed and analyzed several deletion mutants, including a partial surR knockout, under varying conditions. Our results show that hydrostatic pressure modulates the expression of energy metabolism genes and that SurR is essential for activating the hydrogenogenic gene cluster, even in sulfur-rich environments. Under sulfur limitation, the membrane-bound sulfur-reducing complex (MBS) is required for normal growth. These regulatory patterns expand current models derived from non-piezophilic species such as Pyrococcus furiosus and Thermococcus kodakarensis. Overall, our findings indicate that hydrostatic pressure shapes SurR function in T. barophilus, reflecting its adaptive plasticity in extreme environments.